PENGARUH LINGKUNGAN BELAJAR DAN DISIPLIN BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X IIS PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 4 PEKANBARU - Novita Silvia; Suarman Suarman; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of the learning environment and the discipline of learning on student learning outcomes in Economics subjects at Pekanbaru 10 Public High School. This research uses descriptive quantitative method. Population in this study is IIS class X students totaling 131 people and the sample is obtained by using proportional random sampling technique resulted 99 respondents. Data is collected using a question. Data analysis techniques used are Descriptive Analysis and Multiple Linear Regression Analysis using of SPSS version 16.0. The results showed that the learning environment has a significant effect on student learning outcomes which obtained tcount 3,150> t table 1,660 and significant value 0,000 <0,05. Learning discipline has a significant effect on student learning outcomes which obtained tcount 2,297> t table 1,660 and significant value 0,000 <0,05. Simultaneously there is a significant influence between the learning environment and learning discipline of students with learning outcomes which obtained fcount 16.735> ftabel 3.09 and a significant value of 0.000 <0.05. The multiple linear regression equation obtained in this study is Y = 49,795 + 0,142X1 + 0,183X2. It is concluded that of this study indicate the learning environment and learning discipline affect the learning outcomes of economics subjects in the X IIS class of SMA Negeri 4 Pekanbaru. This means that the higher the learning environment and student learning discipline will improve student learning outcomes. Thus to improve student learning outcomes in need of support from teachers and students themselves in the form of learning environment and learning discipline. Keywords: Learning Environment, Learning Discipline, Learning Outcomes